Localization of Secondary Metabolites in Relict Gymnosperms of the Genus Sequoia In Vivo and in Cell Cultures In Vitro, and the Biological Activity of Their Extracts - Rima N. Kirakosyan; Elena A. Kalasnikova; Elizaveta A. Bolotina; Abdulrahman Saleh; Anastasiya A. Balakina; Svetlana M. Zaytseva (Life)
In order to scientifically search for new sources of secondary metabolites with valuable qualities for phytopharmacognosy, tasks requiring a step-by-step solution were set. The primary task is the development of technologies for obtaining in vitro highly productive biomass of cells of relict gymnosperms of the genus Sequoia, capable of accumulating various classes of secondary metabolites. The study of the accumulation and localization of secondary metabolites allowed us to evaluate the biological activity and cytotoxicity of in vitro Sequoia cultures. In our study, histochemical methods were used to determine the localization of secondary compounds (phenolic and terpenoid in nature) in plant tissues. Secondary metabolites—polyphenols, catechins, and terpenoids—are mainly localized in the epidermal, parenchymal, and conductive tissues of Sequoia leaves and stems. In callus and suspension cultures of Sequoia, secondary metabolites were localized in cell walls and vacuoles. The mineral composition of the nutrient medium (MS and WPM), the light source (photoperiod), and the endogenous content of polyphenols in the primary explant influenced the initiation and growth characteristics of the in vitro culture of Sequoia plants. Inhibition of growth in suspension cultures on the WPM nutrient medium was noted. The cultivation of Sequoia cell lines at a 16 h photoperiod stimulated the formation of polyphenols but had a negative effect on the growth of callus cultures. Extractive substances obtained from intact and callus tissues of evergreen Sequoia demonstrate high biological (fungicidal) activity and cytotoxicity. The inhibitory effect on Fusarium oxisporum was noted when 200 mg/L of Sequoia extract was added to the nutrient medium. Extracts of redwood callus cultures were low in toxicity to normal FetMSC cells but inhibited the growth of lines of “immortal” cervical HeLa cancer cells and human glioblastoma A172. Intact tissues of Sequoia plants and cell cultures initiated from them in vitro are producers of secondary metabolites with high biological activity.